Immunohistochemistry in the pathologic diagnosis and management of thyroid neoplasms - Crescenzi, Anna; Baloch, Zubair (Frontiers in Endocrinology, 2023)
The use of immunohistochemistry cannot be underscored in the everyday practice of thyroid pathology. It has evolved over the year beyond the traditional confirmation of thyroid origin to molecular profile and predicting clinical behavior. In addition, immunohistochemistry has also served to implement changes in the current thyroid tumor classification scheme. It is prudent to perform a panel of immunostains and the immunoprofile be interpreted in light of the morphologic features. Immunohistochemistry can also be easily performed in the limited cellularity specimen preparation generated from a thyroid fine-needle aspiration, however, this will require laboratory validation to avoid any diagnostic pitfalls. This review discusses the application of immunohistochemistry in thyroid pathology with focus on cytologic preparations.